God Gave Us Easter - Bergren, Lisa Tawn; Bryant, Laura J. (Colorado Springs, Colo. : WaterBrook Press, 2012)
Little Cub talks with her father and learns about God's design for the Easter season and what it really means to Little Cub and her polar bear family.
Keywords: Easter stories; Christian life -- Juvenile fiction; Polar bear -- Juvenile fiction; Bears -- Juvenile fiction; Easter -- Fiction; Christian life -- Fiction; Polar bear -- Fiction; Bears -- Fiction